Analysis of Service Quality Factors of Surabaya Single Window Website Using E-Govqual and IPA Models - Apriliana Latifah Hanum; Tri Lathif Mardi Suryanto; Arista Pratama (Eduvest - Journal of Universal Studies, 2025)
The development of digital technology has encouraged the government to provide electronic-based public services, including through the Surabaya Single Window (SSW) website which provides online licensing and non-licensing services. However, amidst the increasing use of digital services, various complaints are still found from the public regarding the accuracy of information, system reliability, and the limitations of the interactive features provided. The main problem in this study is whether the quality of SSW website services has met user expectations, and what factors are the priority for improvement. This study aims to evaluate the quality of SSW services based on the E-Govqual model which includes six dimensions: ease of use, trust, interaction environment functionality, reliability, content and display of information, and citizen support. This study uses a descriptive quantitative approach by distributing questionnaires to 400 respondents who are residents of Surabaya City, and data analysis using the Importance Performance Analysis (IPA) method. The results of the study show that all dimensions have negative gap values, indicating that service performance has not fully met user expectations. Several indicators such as calculation simulations, timely service, and information accuracy are in the top priority quadrant for improvement. This study provides strategic recommendations for the government to improve crucial service aspects and maintain indicators that have been assessed well by users.